Transforming Livelihoods: AICCRA Zambia Empowers Smallholder Fish Farmers with Climate-Smart Aquaculture Solutions - Manoti, Dismas; Kakwasha, Keagan; Kikulwe, Enoch; Chinkwanda, George; Chinembiri, Evans (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
AICCRA Zambia is scaling access to and use of climate-smart services and innovations to help Zambian farmers and communities safeguard their livelihoods in the face of climate change. AICCRA is Accelerating Impacts of CGIAR Climate Research for Africa. Climate change is threatening Zambia’s aquaculture and livestock systems, impacting agriculture businesses and undermining livelihoods. It is increasingly urgent for fish farmers in Zambia to be able to anticipate climate-related events and take appropriate preventative actions. AICCRA Zambia is working with local and national partners to scale actionable climate information, de-risk investments into agribusinesses and boost the knowledge and use of climate-smart aquaculture technologies which promote gender and social inclusion.